SCALES, DYNAMICS AND SPATIAL PATTERNS OF FORCED INTERNAL DISPLACEMENT OF POPULATION IN THE EAST OF UKRAINE - LOHVYNOVA, Maryna (Ekonomichna ta Sotsialna Geografiya, 2020)
Eastern Ukraine is a region where for the first time during the time of independent Ukraine in 2014 forced internal migration of the population arose, as well as a region that accepted almost 2/3 of all internally displaced persons (IDPs). The uneven concentration of IDPs in the Eastern region of Ukraine creates an excessive burden on the labor market, infrastructure, and local authorities. The purpose of the study is to identify and explain the spatio-temporal features of forced internal displacement in the East of Ukraine from 2014 to 2019. The study is based on statistics from the Ministry of Social Policy of Ukraine, Donetsk, Luhansk and Kharkiv regional state administrations. The following research methods were used in the work: mathematical-statistical, analysis and synthesis method, generalization, description, systematization, retrospective, graphic, cartographic and cartographic modeling. The study of the dynamic aspects of IDPs in the region revealed a gradual decrease in the dynamics of the number of IDPs, which may be due to the successful integration of forced migrants into host communities, the reluctance to confirm the status of IDPs through bureaucratic procedures and periodic inspections, or with repeated displacement. Analysis of the spatial characteristics of IDPs by city, city councils and districts of the Eastern region of Ukraine allowed us to distinguish three categories of IDPs depending on their location in the region. Among them: the overwhelming majority – IDPs of retirement age, who are guided by the factor of territorial proximity, are registered in the areas closest to the demarcation line, although most of them actually live in territory beyond the control of Ukraine, and carry out periodic trips through the demarcation line; IDPs of working age, which are mainly located in cities for the purpose of employment and access to quality services; the most vulnerable and socially unprotected categories living in places of compact accommodation of IDPs, but their minority. The age structure of IDPs is considered, the predominant age group of all regions of Eastern Ukraine are pensioners. The regions with the highest share of pensioners and a large demographic burden of pensioners and IDP children on the local population are identified. In particular, in some areas of the Luhansk region, the number of IDP pensioners is almost double that of the local population of all age groups. This situation requires special attention, since an excessive concentration of IDP pensioners in these territories can lead to a deep demographic crisis. So, the socio-geographical analysis of the spatial distribution of IDPs in the Eastern region of Ukraine shows the real extent of forced internal population displacement in the region, and the analysis of the age structure of IDPs allows one to determine the options for the impact of forced migrations on the socio-economic development of host regions and serves as an indicator of the need to adopt appropriate programs or decisions regarding the improvement of the situation of IDPs.

Східна Україна – регіон, де вперше за часів незалежної України у 2014 р. виникли вимушені внутрішні міграції населення, а також регіон, який прийняв майже 2/3 усіх внутрішньо переміщених осіб (ВПО). Нерівномірна концентрація ВПО по території Східного регіону України створює надмірне навантаження на ринок праці, об’єкти інфраструктури, органи місцевої влади. Мета дослідження полягає у виявленні та поясненні просторово-часових особливостей вимушеного внутрішнього переміщення населення на Сході України з 2014 по 2019 рр. Дослідження базується на статистичних даних Міністерства соціальної політики України, Донецької, Луганської та Харківської обласних державних адміністрацій. У роботі використано такі методи дослідження: математико-статистичний, метод аналізу та синтезу, узагальнення, опису, систематизації, ретроспективний, графічний, картографічний та картографічного моделювання. В результаті дослідження динамічних аспектів ВПО в регіоні виявлено поступове зменшення динаміки їх чисельності, що може бути пов’язано з успішною інтеграцією вимушених мігрантів у приймаючі громади, небажанням підтверджувати статус ВПО через бюрократичні процедури і періодичні перевірки або з повторним переміщенням. Аналіз просторових особливостей ВПО у розрізі міст, міських рад та районів Східного регіону України дозволив виділити три категорії ВПО в залежності від їх розміщення у регіоні. Серед них: переважна більшість – ВПО пенсійного віку, які орієнтуються на фактор територіальної близькості, реєструються у найближчих до лінії розмежування районах, хоча більшість із них фактично проживає на непідконтрольній Україні території, та здійснюють періодичні поїздки через лінію розмежування; ВПО працездатного віку, які розміщуються переважно у містах з метою працевлаштування та доступу до якісних послуг; найбільш вразливі та соціально незахищені категорії ВПО, які проживають у місцях компактного проживання населення, однак їх меншість. Розглянуто вікову структуру ВПО, переважаючою віковою групою усіх областей Східного регіону є пенсіонери. Визначено регіони із найвищою часткою пенсіонерів та надмірним демографічним навантаженням пенсіонів та дітей з числа ВПО на місцеве населення. Зокрема, у деяких районах Луганської області чисельність пенсіонерів ВПО майже вдвічі перевищує чисельність місцевого населення всіх вікових груп. Така ситуація потребує особливої уваги, оскільки надмірна концентрація пенсіонерів ВПО на цих територіях може призвести до глибокої демографічної кризи.Отже, проведений суспільно-географічний аналіз просторового розподілу ВПО у Східному регіоні України показує реальні масштаби вимушеного внутрішнього переміщення населення в регіоні, а аналіз вікової структури ВПО дозволяє визначити варіанти впливу вимушених міграцій на соціально-економічний розвиток приймаючих регіонів та виступає індикатором необхідності прийняття відповідних програм або рішень щодо покращення становища ВПО.
МАСШТАБИ, ДИНАМІКА ТА ПРОСТОРОВІ ОСОБЛИВОСТІ ВИМУШЕНОГО ВНУТРІШНЬОГО ПЕРЕМІЩЕННЯ НАСЕЛЕННЯ НА СХОДІ УКРАЇНИ
Keywords: forced migration; internal displacement of the population; internally displaced persons (IDPs); migrants; Eastern Ukraine; military conflict; demographic burden; вимушена міграція; внутрішнє переміщення населення; внутрішньо переміщені особи (ВПО); мігранти; Східна Україна; воєнний конфлікт; демографічне навантаження